0 - Introduction - Mabizela, Mahlubi (Journal of Higher Education in Africa, 2007)
The growth of private provision of higher education in recent years is a phenom- enon experienced the world over, but especially in Africa, Central and Eastern Europe, Asia and Latin America. Some of these regions had very little or no pri- vate higher education before the 1990s. As elsewhere in the world, the private provision of higher education in Africa is largely not new but has had antecedents. Hence, it is appropriate for some countries to refer to the latest wave as a resur- gence rather than as a surge of the sector. Indeed, the private higher education surge happens in the context where the public sector is dominant and state poli- cies do not cater for the private sector. This partly leads to private institutions having to deal with issues of legitimacy. Despite this, their prominence has rekin- dled debates on what is higher education, higher education as a public/private good, and quality, among other issues. This introductory article deals with these issues as a way of providing a background to all the other themes dealt with individually by other papers in this volume. It outlines the purposes and objectives of this special issue and gives a detailed summary of each article contained herein.